Bangladesh Development Update, April 2013 - World Bank (Washington, DC, 2014)
Weak exports and investments resulting from the impact of the euro-area crisis, domestic supply constraints, and intensified strikes and unrests underpin the growth slowdown. Strong remittances and robust service sector performance are expected to help maintain growth at a still healthy level. Increasingly fragile political stability does not bode well for revival of investment needed to accelerate growth. A broad-based declining inflation trend appears to be gaining ground. Average (twelve-monthly-moving) inflation has declined steadily over the past ten months, from a peak of nearly 11 percent in February 2012 to 8 percent in March 2013, reflecting declines in both food and non-food inflation. Favorable international commodity prices, a stable exchange rate and monetary tightening contributed to lowering inflation.